Modelling human skin: organotypic cultures for applications in toxicology, immunity, and cancer (2021)
ABSTRATC: Animal models are important tools to better understand different skin processes. These are widely used for chemical hazard identification and to study skin-related pathologies. Despite the complexity they offer, animal skin is not a perfect model of human skin. This and the growing ethical concern about animal experimentation has led to the development of alternative methods that are in line with the 3 rules guidelines (reduction, refinement and replacement of animals in experiments) within the seventh amendment to the EU Cosmetics Directive 76/768/EEC. One of these alternatives are human skin explant models. Such models contain the main cellular components, a skin barrier function, and a mature stratum corneum, and are therefore highly suitable to replace animal testing. However, they rely on a regular supply of fresh tumor biopsies of proper size, limiting their use in drug testing assays. Another alternative, in vitro bi-dimensional (2D) skin models, have been produced as well, but they are restricted by the lack of similarity to the skin in vivo structure, phenotype, and behavior. Therefore, three-dimensional (3D) skin substitutes represent a powerful alternative to animal testing. Over the last years, many elegant studies have developed 3D models composed of human skin cells and extracellular matrix components. Still, most of them are limited to one cellular type, neglecting the contribution of other important elements like the dermis, the immune component, or interaction between different cell types. Therefore, to better understand skin behavior and responses, models that more faithfully mimic the human skin are needed. In this thesis, we aimed to develop 3D fibrin-based human skin equivalents for applications in the fields of toxicology, immunology, and cancer, containing both the dermal and epidermal compartments.